2014
DOI: 10.1371/journal.pone.0104283
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Systematic Bias in Transcriptome Data from Human Peripheral Blood Mononuclear Cells for Transportation and Biobanking

Abstract: Transportation of samples is essential for large-scale biobank projects. However, RNA degradation during pre-analytical operations prior to transportation can cause systematic bias in transcriptome data, which may prevent subsequent biomarker identification. Therefore, to collect high-quality biobank samples for expression analysis, specimens must be transported under stable conditions. In this study, we examined the effectiveness of RNA-stabilizing reagents to prevent RNA degradation during pre-analytical ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Library quality was assessed as previously described. 65 For cluster generation with the HiSeq SR Cluster Kit v4 cBot (Illumina), six libraries were mixed in equimolar concentrations and were loaded into flow cells. Sequencing was performed in the HiSeq 2500 system (Illumina) with the HiSeq SBS Kit v4 (single-end 125-bp reads).…”
Section: Methodsmentioning
confidence: 99%
“…Library quality was assessed as previously described. 65 For cluster generation with the HiSeq SR Cluster Kit v4 cBot (Illumina), six libraries were mixed in equimolar concentrations and were loaded into flow cells. Sequencing was performed in the HiSeq 2500 system (Illumina) with the HiSeq SBS Kit v4 (single-end 125-bp reads).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Ohmomo et al found that after storage at −80°C for a period of time, the quality of the RNA extracted from the peripheral blood mononuclear cells (PBMCs) with RNA protective agent was significantly higher than from the PBMCs without RNA protective agent. 11 However, these methods of blood storage are limited by some objective conditions such as storage equipment, reagents, sample collection and the professionalism of interim management personnel. They may be difficult for onerous clinical procedures of for some more remote transporting after sampling.…”
Section: Introductionmentioning
confidence: 99%
“…We prepared cDNA libraries from 150 ng of total RNA with TruSeq RNA sample Preparation Kit v2 (Illumina, San Diego, CA, USA) for the RNA-Seq, and then carried out fragment size and expression analyses as previously described 22 . For RNA-Seq, equimolar mixtures of the twelve libraries were loaded into four flow cells for cluster generation using a TruSeq Rapid SR Cluster Kit-HS (Illumina) and sequenced on a HiSeq2500 system (Illumina) using a TruSeq Rapid SBS Kit-HS (Illumina), generating 1 × 101 bp reads.…”
Section: Methodsmentioning
confidence: 99%